2022
DOI: 10.3390/cancers14194631
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Biomarkers for Immunotherapy in Patients with Hepatocellular Carcinoma: Current Knowledge and Future Perspectives

Abstract: The treatment perspectives of advanced hepatocellular carcinoma (HCC) have deeply changed after the introduction of immunotherapy. The results in responders show improved survival compared with Sorafenib, but only one-third of patients achieve a significant benefit from treatment. As the tumor microenvironment exerts a central role in shaping the response to immunotherapy, the future goal of HCC treatment should be to identify a proxy of the hepatic tissue condition that is easy to use in clinical practice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 213 publications
0
16
0
Order By: Relevance
“…Thus, scientific debate has arisen regarding the usefulness of returning to the quest for molecular biomarkers for HCC, in particular after the advent of the new immunotherapies. 6,7 In this regard, the article by Brar et al provides a relevant meeting point between using machine learning-based strategies and identifying molecular biomarkers for the management of patients with HCC.…”
Section: E D I T O R I a L Machine Learning And Biomarkers In Hepatoc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, scientific debate has arisen regarding the usefulness of returning to the quest for molecular biomarkers for HCC, in particular after the advent of the new immunotherapies. 6,7 In this regard, the article by Brar et al provides a relevant meeting point between using machine learning-based strategies and identifying molecular biomarkers for the management of patients with HCC.…”
Section: E D I T O R I a L Machine Learning And Biomarkers In Hepatoc...mentioning
confidence: 99%
“…Although this process may seem straightforward, clinicians struggle daily to solve complex, and sometimes uncertain, diagnoses without having the possibility to rely on molecular data as often happens for other cancers. Thus, scientific debate has arisen regarding the usefulness of returning to the quest for molecular biomarkers for HCC, in particular after the advent of the new immunotherapies 6,7 . In this regard, the article by Brar et al provides a relevant meeting point between using machine learning‐based strategies and identifying molecular biomarkers for the management of patients with HCC.…”
mentioning
confidence: 99%
“…Currently, systemic therapy for patients with advanced HCC includes molecularly targeted agents, immune checkpoint inhibitors, or a combination of both (2)(3)(4). However, a substantial proportion of patients have yet to benefit from systemic therapy (5,6). Recent studies have identified several novel biomarkers that can predict HCC prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Discovering biomarkers that can accurately predict HCC prognosis will be a major research topic in the management of HCC treatment in the near future. 10 As one of the most common RNA modifications, N7-methylguanosine (m7G) refers to the RNA methylation of guanine at the N7 position and exists in about 0.4% of guanosine. 11 Great progress has been made in studying the regulation of m7G in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that immunotherapy could greatly improve the survival rate of HCC in comparison with sorafenib, but only one‐third of patients benefit significantly from the treatment. Discovering biomarkers that can accurately predict HCC prognosis will be a major research topic in the management of HCC treatment in the near future 10 …”
Section: Introductionmentioning
confidence: 99%